Pembuatan Minuman Kurma Rempah Instan Berbahan Dasar Kurma Kering dan Serbuk Rempah - Onie Anjani; Niken Purwidiani; Ita Fatkhur Romadhoni; Lucia Tri Pangesthi (Pusat Riset dan Inovasi Nasional, 2024)
This research is an experiment in making spice powder and dried dates as a product innovation in instant drinks. This research aims to find out; 1) data on product sensory test results with the criteria of color, aroma, texture, taste, viscosity and preference; 2) the antioxidant content, carbohydrates, calories, fiber and water content are carried out in laboratory tests; and 3)selling price per package. This research is an experimental study with a factor pattern comparing the amount of dried dates and spice powder with 3 treatments, namely (15g:10g), (15g:15g), and (15g:20g). Data collection was carried out using the observation method through sensory tests with the data analysis method of the single ANOVA test and the Duncan follow-up test. The research results show; 1)spice powder with the addition of dried dates produces a product with sensory properties, cream color, sharp spice aroma, smooth texture. Meanwhile, the brewed drink produces sensory characteristics of a dark brown color, sharp spice aroma, soft date texture, sweet taste (taste of spices and dates), viscosity of the liquid date spice drink. The product was well received by the panelists, namely a ratio of 15 grams of spices; 20 grams of dried dates; 2)based on the results of the sensory test, it shows that the sample in the ratio of 15 grams; 20 grams of brewed drink contains carbohydrates; 26.91%, fiber; 1.10%, antioxidant; 98.62/100g, calories; 124.80kcal/100ml%. While powder contains carbohydrates; 23.10%, fiber; 8.01%, antioxidant; 102.10/100g, calories; 241.5080kcal/100g, water; 4.18%; and 3)the selling price of spice powder with the addition of dried dates is known to be IDR 9,000 per 35 gram sachet.